Early Removal of Scleral Buckle: Doi: 10.36351/pjo.v38i2.1357 - Usman, Nida; Haider, Muhammad Ali (Pakistan Journal of Ophthalmology, 2022)
Purpose: To study the outcomes of early removal of segmental buckle on visual acuity, retinal status, and astigmatism. Study Design: Interventional case series Place and Duration of Study: Mayo hospital, from February 2018 to July 2018. Methods: Ten patients fulfilling the inclusion criteria were recruited. All the patients underwent segmental radial sponge with cryoretinopexy, with or without drain and intraocular gas tamponade as per need. Post-operative follow ups were at 1st week, 4th week and 6th week. Sponge was removed at 6th week after making sure that the retina was attached. Follow ups after buckle removal were planned at 1st week, 1st month and 3rd month. Improvement in VA, retinal status and astigmatism were noted. The commonest reason for the explant removal was infection followed by pain. Normality was checked through Shapiro-Wilk’s W-test and the normality criteria was met so paired sample t-test was used to assess the significance of astigmatism pre and post-surgery. Results: The average age was 32.30 ± 16.75 years (range, 03 – 61 years). Anatomical success was achieved in 100%. Visual acuity improved in all patients. Moreover, early removal of buckle reduced astigmatism and further improvement in vision was also noted. Pre and post-surgical vision improvement was statistically significant with p-value of 0.000. After removal of buckle, improvement of astigmatism was also statistically significant p-value 0.004. Conclusion: The early removal of scleral explant not only provides symptomatic relief to the patients, but is also associated with marked improvement in visual acuity was noted. Key Words: Visual Acuity, Astigmatism, Retinal Detachment, Segmental Scleral Buckle.